2008
DOI: 10.1097/fbp.0b013e3282f3d093
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement magnitude modulates the rate-dependent effects of fluvoxamine and desipramine on fixed-interval responding in the pigeon

Abstract: Some doses of fluvoxamine can decrease ethanol-maintained behavior more than food-maintained behavior. This might be explained by differences in reinforcement magnitude. In a previous study, the effects of fluvoxamine on fixed-ratio responding did not depend upon reinforcement magnitude. Response rates, however, differed with reinforcement magnitude. These differences in response rates might explain the failure to observe differences in the potency of fluvoxamine with changes in reinforcement magnitude. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…However, we have demonstrated that fluvoxamine effects are unlikely to depend on the magnitude of reinforcement (Lamb and Ginsburg, 2005, 2008; Ginsburg and Lamb, 2008). The extent to which varenicline effects could be influenced by the relative frequencies of reinforcement remains unknown.…”
Section: Discussionmentioning
confidence: 81%
“…However, we have demonstrated that fluvoxamine effects are unlikely to depend on the magnitude of reinforcement (Lamb and Ginsburg, 2005, 2008; Ginsburg and Lamb, 2008). The extent to which varenicline effects could be influenced by the relative frequencies of reinforcement remains unknown.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study showed that nicotine also increased the number of completed ratios on a progressive ratio schedule of visual stimulus presentation (Chaudhri et al 2007), suggesting that nicotine does more than merely increase low response rates. Nevertheless, more research will be necessary to test whether nicotine increases low rates of responding or whether such increases are specific to parameters of the reinforcing stimuli (Lamb and Ginsburg 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Work performed with pigeons demonstrated that reinforcement magnitude can modulate the rate-dependent effects of fluvoxamine and desipramine (Lamb and Ginsburg, 2008). In that study, pigeons responded under a multiple fixed-interval schedule reinforced by 2-, 4-, or 8-sec access to food.…”
Section: Introductionmentioning
confidence: 99%